Repatriation of South Sudanese refugees from the West Nile districts, Uganda. What do we learn from the process? - Komakech, Henry; Orach, Christopher Garimoi (African Health Sciences, 2022)
Introduction: Repatriation is a fundamental and often preferred solution to the refugee crisis around the world. This study explored the process of repatriation of the South Sudanese refugees from the West Nile districts in Uganda. Methods: This was a retrospective analysis of the process of repatriation of refugees in three west Nile refugee districts of Adjumani, Arua, and Moyo, Uganda. Both qualitative and qualitative data were collected. Results: The findings showed that several stakeholders were involved in the repatriation exercise including the government at central and district levels, United Nations agencies and non-governmental organizations, and refugee communities. The key steps undertaken during repatriation include information and education campaigns to promote returns focussing on security and socio-economic conditions in South Sudan and the facilitation of confidence-building visits in the areas of origin. During the repatriation exercise, key interventions provided included health care screening and treatment, and the provision of reintegration support services including the provision of food security items and cash allowances. Conclusions: The findings highlight the fundamental steps followed during a well-planned, structured, and effective repatriation of South Sudanese refugees from Uganda. Understanding repatriation requires an appreciation of how it is implemented to support offering an effective, durable, and lasting solution to refugees to promote their health and welfare.
Keywords: Refugee; South Sudan; Uganda; process of repatriation; repatriation; west Nile